Migration as a Mexico-United States binational issue - Payán, Luis Antonio (Cuadernos Fronterizos, 2024)
In June 2012, a novel phenomenon surprised everyone—a caravan of several thousand migrants marching toward the U.S.-Mexico border. Since then, the “caravanization” of migration, that is, large numbers of migrants that include single individuals, family units, and even unaccompanied minors, from multiple nationalities, has been a feature of the immigration landscape. As individuals swarmed in Latin America, the Middle East, and Sub-Saharan Africa, to march toward developed countries—especially the European Union and the United States, countries like Mexico, Turkey, and Morocco have become an obligated passageway.